Outlook on Global Oilseed Sector: Research for Development Opportunities - Swamikannu, Nedumaran; Okori, Patrick; Mushoriwa, Hapson; Kumar, Ashok Are; Gupta, Shashi Kumar; Kumar, Shalander; Ravula, Padmaja; Dar, Mansoor; Pasupuleti, Janila; Hauser, Michael; Gumma, Murali Krishna; Haile, Desmae; et al. (2024)
The document details the rationale for the inclusion of oilseeds in the extended research portfolio of ICRISAT. The expansion of the Institute’s research portfolio is a strategic demand-driven response of ICRISAT to the emerging market dynamics of oilseeds globally. Oilseed crops are known for thriving in the drylands as they fit in the low-input cereal-based cropping pattern and come with the comparative advantage of being highly remunerative. The expansion of the research portfolio will increase the operational efficiency of the Institute, leveraging on the rich experience and expertise and state-of-the-art technologies that the Institute possesses and help the Institute deliver better on its mission of enhancing and empowering the livelihoods of the smallholder farmers in the semi-arid tropics. The Institute will focus on building inclusive value chains, and breeding for disease-resistant oilseed crop varieties for the targeted agroecologies rather than reinventing the wheel. It will only further the basic research that has been already done using its strong national and international partnerships in both public and private sectors. The Institute aspires and envisions replicating the success stories in the seed sector for oilseed crops using the Hybrid Parents Research Consortium (HPRC) model for millets. ICRISAT’s experience and expertise in developing the first high oleic acid groundnut varieties will help in bringing about similar technological breakthroughs catering to the emerging market demand for the selected oilseed crops. The relevance of oilseed crops to the economies of Asia and Africa, the projected trends in their increasing domestic demand in the future, historical trends in the net trade balance of oilseeds in Asian and African semi-arid tropics, and the persistent yield gaps in oilseed in the drylands necessitate prioritization of increased Research and Development (R&D) on these crops. Over five decades, ICRISAT has successfully addressed comparable issues in its current mandate crops by using advanced technologies co-developed with domestic and international partners. Therefore, considering the Institute’s strong presence in both Asia and Africa, the expansion of ICRISAT’s research portfolio to include oilseeds in addition to the current six mandate crops is expected to help the Institute deliver far-reaching higher impacts in the drylands and thereby increasingly contribute to the progress made globally towards achieving the Sustainable Development Goals (SDGs).